2017
DOI: 10.1038/nature24488
|View full text |Cite
|
Sign up to set email alerts
|

A compositional tipping point governing the mobilization and eruption style of rhyolitic magma

Abstract: The most viscous volcanic melts and the largest explosive eruptions on our planet consist of calcalkaline rhyolites. These eruptions have the potential to influence global climate. The eruptive products are commonly very crystal-poor and highly degassed, yet the magma is mostly stored as crystal mushes containing small amounts of interstitial melt with elevated water content. It is unclear how magma mushes are mobilized to create large batches of eruptible crystal-free magma. Further, rhyolitic eruptions can s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
65
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 86 publications
(70 citation statements)
references
References 110 publications
5
65
0
Order By: Relevance
“…The current models are applicable within the compositional space that they are based upon, but some compositional regions (e.g. peralkaline compositions) still remain unmapped and the models struggle to repro− duce measured viscosity values [Giordano et al, 2006, Di Genova et al, 2017. Those formulations also put in evidence that the role of water (H 2 O) dissolved in the melt is counterintuitive being opposite to that of net− work modifier cations.…”
Section: T -Dependent Models For Predicting Melt Viscositymentioning
confidence: 99%
“…The current models are applicable within the compositional space that they are based upon, but some compositional regions (e.g. peralkaline compositions) still remain unmapped and the models struggle to repro− duce measured viscosity values [Giordano et al, 2006, Di Genova et al, 2017. Those formulations also put in evidence that the role of water (H 2 O) dissolved in the melt is counterintuitive being opposite to that of net− work modifier cations.…”
Section: T -Dependent Models For Predicting Melt Viscositymentioning
confidence: 99%
“…GRN samples may have suffered oxidation during μXANES (Cottrell et al 2018), therefore their reported Fe oxidation state values are not considered further and the samples are only used to explore the effects of composition on redox changes during EPMA. The high-silica glasses range from peralkaline (FSP in Di Genova et al 2016, andPSG in Di Genova et al 2013) to calcalkaline (Y in Di Genova et al 2017a, andPSB in Riker et al 2015), with both anhydrous (FSP and Y) and hydrous (PSG and PSB) glasses.…”
Section: Samplesmentioning
confidence: 99%
“…Raman spectroscopy was used to detect the presence of nanolites before and after electron beam irradiation as nanolites alter the Raman spectra of silicate glasses. Magnetite nanolites produce a peak at ~670 cm -1 , which also decreases the intensity of the surrounding silicate peaks (Di Genova et al 2017a, 2017b. Carbon coats were removed prior to analysis.…”
Section: Raman Spectroscopymentioning
confidence: 99%
See 2 more Smart Citations